Reformasi Kelembagaan Ombudsman: Prospek Cabang Keempat Pemerintahan Indonesia untuk Akuntabilitas dan Pengawasan Hak Warga Negara - Claudya Mareshky; Kanaya Ayudya Putri; Ngesti Mukti Rezeki (Kampus Akademik Publiser, 2024)
Abstract. Institutional reform of the Ombudsman in Indonesia offers significant prospects for strengthening accountability and improving oversight of government performance. This Journal examines the potential establishment of the Ombudsman as a fourth branch of government, aimed at ensuring the protection of citizens' rights as well as increasing transparency in state administration. Journal highlights the strategic role of the Ombudsman in the context of modern democracies, where independent oversight is key to the success of responsive and accountable governance. The findings show that strengthening the Ombudsman's position can contribute significantly to reducing abuse of power and increasing public trust in government. The journal also discusses the challenges faced in implementing these reforms, including bureaucratic resistance and the need for legislative change. Thus, the institutional reform of the Ombudsman is expected to be a step forward in realizing better governance, transparency, and responsiveness to citizens' needs. Keywords: Ombudsman, Fourth Branches, Accountability, Governance Abstrak. Reformasi kelembagaan Ombudsman di Indonesia menawarkan prospek signifikan untuk memperkuat akuntabilitas dan meningkatkan pengawasan terhadap kinerja pemerintahan. Jurnal ini mengkaji potensi pembentukan Ombudsman sebagai cabang keempat pemerintahan, yang bertujuan untuk memastikan perlindungan hak-hak warga negara serta meningkatkan transparansi dalam penyelenggaraan negara. Jurnal ini menyoroti peran strategis Ombudsman dalam konteks demokrasi modern, di mana pengawasan independen menjadi kunci keberhasilan pemerintahan yang responsif dan akuntabel. Temuan menunjukkan bahwa penguatan kedudukan Ombudsman dapat berkontribusi signifikan terhadap pengurangan penyalahgunaan kekuasaan dan peningkatan kepercayaan publik terhadap pemerintah. Jurnal ini juga membahas tantangan yang dihadapi dalam implementasi reformasi ini, termasuk resistensi birokrasi dan kebutuhan akan perubahan legislatif. Dengan demikian, reformasi kelembagaan Ombudsman diharapkan dapat menjadi langkah maju dalam mewujudkan pemerintahan yang lebih baik, transparan, dan responsif terhadap kebutuhan warga negara. Kata Kunci: Ombudsman, Empat Cabang, Akuntabilitas, Pemerintahan